Study on the constructions of optimal almost quaternary sequences with period 2q - Xiuping PENG; Huipu JI; Deliang ZHENG; Xiaoxia NIU (Tongxin xuebao)
Based on the Chinese remainder theorem and cyclotomic classes of order 4,the constructions of almost quaternary sequences with period N=2q (where q is an odd prime) was studied.According to the number of “0” in the two positions y(0) and y(q),three types of optimal almost quaternary sequences with optimal balance property and out-of-phase autocorrelation values as{0,-2},{0,2,-2} and {0,-2,-2i,2i} were constructed respectively.Through these constructions,all the almost quaternary sequences constructed are balanced and optimal.These constructed sequences extend the existence range of the balanced optimal quaternary sequences and provide more optimal sequences for practical applications.